23. FACTORS RELATED TO CANDIDA SPP INFECTION IN LOWER GENITAL TRACT AMONG MARRIED WOMEN IN QUANG TRACH DISTRICT, QUANG BINH PROVINCE (Vietnam Journal of Community Medicine, 2024)
Objectives: Cross-sectional descriptive study with the objective of investigating certain factors related to Candida spp infections among 275 married women aged 18 to 49 in Quang Trach district, Quang Binh province, from January 2023 to October 2023.Research methods: Data was collected through direct interviews using pre-designed questionnaires, combined with gynecological examinations and vaginal discharge tests for fungi using staining and culture techniques.Results: Women with education levels of high school or below had a 2.13 times higher rate of Candida spp infection compared to those with education levels above high school (95% CI = 1.062-4.270; p = 0.031); women using contraceptive methods had a 1.9 times higher rate of Candida spp infection compared to those not using them (95% CI = 1.008-3.606; p = 0.045); women working in hot and humid environments had an 3.32 times higher rate of Candida spp infection compared to those working in normal environments (95% CI = 1,73-40,04; p < 0,05).
Keywords: Infection of Candida spp; vaginitis